Preschool Motor Development Predicting High School Health-Related Physical Fitness: A Prospective Study. Issue 1 (August 2014) - Vlahov, Eric; Baghurst, Timothy M.; Mwavita, Mwarumba
To address the obesity epidemic there is an increasing effort to emphasize physical activity and fitness in adolescence as opposed to fundamental motor skills. However, what effect this might have on health-related fitness is unclear. This study sought to determine the degree to which motor development competencies in preschool could predict high school fitness. In the initial study, participants were 143 male and 139 female preschoolers ( M age = 4.8yr., SD = 0.7) from four preschool programs in suburban area of a Southern state who completed the Test of Gross Motor Development. Eleven years later, 75 boys and 65 girls ( M age = 15.8yr., SD = 0.7) from the original sample were located and completed the AAHPERD Health Related Fitness Test (1.5mile run, sit-up, sit-and-reach, body fat percentage). Test of Gross Motor Development scores were found to be strong predictors for all measures of fitness, but object control skills were more predictive of overall physical fitness than locomotor skills. Therefore, educators should consider teaching sport skill development in early childhood over general activity to improve long-term fitness.